How Do Environmental, Social, and Governance Activities Affect Green Innovation? The Roles of Employees’ Cognition and CEO Leadership - Yuhan Liu; Ji Hong Min; Xiaotian Ji (SAGE Open)
Environmental, social, and governance (ESG) activities, along with green innovation, have become crucial strategies for achieving sustainable development in business. However, the relationship between ESG activities and green innovation remains inconclusive in the current literature. This study aims to clarify this relationship by addressing three key questions: (1) whether ESG activities are linked to green innovation, (2) the mechanisms through which these activities influence green innovation, and (3) the conditions that enhance their effectiveness. Therefore, we integrated the Input-Process-Outcome(IPO) model with leadership theory and collected empirical data through a questionnaire survey of 299 small and medium-sized Chinese manufacturers. The results indicate that each of ESG activities has a positive impact on green innovation, with the social and governance(SG) aspects partially mediated by employees’ cognition, Furthermore, the moderated mediation analysis shows that the strength of this mediation varies depending on the leadership style of the CEO. These findings highlight the critical roles of employees’ cognition and CEO leadership in fostering green innovation through ESG activities, providing new insights into effective management for sustainable development.